Information Technology Pioneers of Aotearoa New Zealand - Carpenter, Brian E.; Manoharan, Sathiamoorthy (IEEE annals of the history of computing, 2025)
This article traces the history of New Zealand’s information technology innovators from the late 19th century until the arrival of the first stored-program computers in 1960, a history that parallels the country’s evolution toward a modern economy. Starting in 1879, various individuals deployed simple racetrack totalisators. At the turn of the century, Donald Murray became a leading figure in automatic telegraphy. As punched card usage blossomed in the 1920s and 1930s, Leslie Comrie moved to the United Kingdom, where he actively promoted scientific computation. By the 1950s, the economy had matured to the point where government, businesses, and universities were eager to join the computer age. We conclude with the stories of some of the first New Zealanders to write software during this booming computer age, and we were privileged to interview three of them.